Gunung Gare Kota Pagar Alam Dengan Konsep Zero Runoff System - Deska Oktariani; Alharia Dinata; Fameira Dhiniati (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2018)
Internal runoff is caused conversion of green land into be constructed where if there is rain with high rainfall intensity then rainfall runoff will become large and trigger water puddle (overflow) because of reduced area to absorb water. Zero runoff rainwater needs to be applied to the building and land use where the runoff volume (input) can be withstand up to 100% and runoff flow volume (outflow) of 0% or maximum of 3% so that it can reduce the impact of decreasing peak floods (water puddle) the purpose is to analyze the runoff of rain water from the roof of building so it can be useful for processing and utilization of rain water and analyze the needs of absorption wells, reservoir and maximum discharge to retention pond. Roof of parcel area of 13.438,24 m2 is 0,88336 m3/s the need of absorption wells in building is as much as 8 units of recharge wells with Ø 100 cm.reservoir that is needed in the building is 45 units of reservoir with size 30m3. The volume of retention ponds to accommodate runoff discharge from the land use area of 273.339,4 m2 and the roof ot the building area of 13.438,24 m2 is equal to 12.259,4 m3/year at Gunung Gare office complex of Pagar Alam city.